Co-production of knowledge in transdisciplinary communities of practice: Experiences from food governance in South Africa - (:unkn) unknown (My University, 2021)
Communities of Practice are sites of social learning for the co-production of knowledge. Building on recent literature on Transdisciplinary Communities of Practice, this article reflects on the experiences of an emergent 'Food Governance Community of Practice' in South Africa that brings together multiple stakeholders to co-produce knowledge to inform local food policy and governance. Our results show the following lessons for managers and participants engaged in establishing similar 'third spaces' for knowledge co-production: 1) make inevitable power asymmetries explicit; 2) the identity of the group should not be built on a particular normative position but emerge from discursive processes and 3) create a balance between supporting peripheral learning and maintaining the specialist cutting edge discussions needed for co-production. Furthermore, the most beneficial legacy of a Community of Practice may not be the outputs in terms of the co-produced knowledge but the development of a cohesive group of stakeholders with a new shared way of knowing.
Keywords: African Research